Angiotensin-Converting Enzyme Inhibitor or Angiotensin Receptor Blocker Use Among Hypertensive US Adults With Albuminuria. Issue 1 (January 2021) - Chu, Chi D.; Powe, Neil R.; McCulloch, Charles E.; Banerjee, Tanushree; Crews, Deidra C.; Saran, Rajiv; Bragg-Gresham, Jennifer; Morgenstern, Hal; Pavkov, Meda E.; Saydah, Sharon H.; Tuot, Delphine S.
Abstract : Since 2003, US hypertension guidelines have recommended ACE (angiotensin-converting enzyme) inhibitors or ARBs (angiotensin receptor blockers) as first-line antihypertensive therapy in the presence of albuminuria (urine albumin/creatinine ratio ≥300 mg/g). To examine national trends in guideline-concordant ACE inhibitor/ARB utilization, we studied adults participating in the National Health and Nutrition Examination Surveys 2001 to 2018 with hypertension (defined by self-report of high blood pressure, systolic blood pressure ≥140 mm Hg or diastolic ≥90 mm Hg, or use of antihypertensive medications). Among 20 538 included adults, the prevalence of albuminuria ≥300 mg/g was 2.8% in 2001 to 2006, 2.8% in 2007 to 2012, and 3.2% in 2013 to 2018. Among those with albuminuria ≥300 mg/g, no consistent trends were observed for the proportion receiving ACE inhibitor/ARB treatment from 2001 to 2018 among persons with diabetes, without diabetes, or overall. In 2013 to 2018, ACE inhibitor/ARB usage in the setting of albuminuria ≥300 mg/g was 55.3% (95% CI, 46.8%–63.6%) among adults with diabetes and 33.4% (95% CI, 23.1%–45.5%) among those without diabetes. Based on US population counts, these estimates represent 1.6 million adults with albuminuria ≥300 mg/g currently not receiving ACE inhibitor/ARB therapy, nearly half of whom do not have diabetes. ACE inhibitor/ARB underutilization represents a significant gap in preventive care delivery for adults with hypertension and albuminuria that has not substantially changed over time. Abstract : Supplemental Digital Content is available in the text.